Identification of a self-paced hitting task in freely moving rats based on adaptive spike detection from multi-unit M1 cortical signals - Hammad, Sofyan H.; Farina, Dario; Kamavuako, Ernest N.; Jensen, Winnie (Frontiers in Neuroengineering, 2013)
Invasive brain computer interfaces may prove to be a useful rehabilitation tool for severely disabled patients. Although some systems have shown to work well in restricted laboratory settings, their usefulness must be tested in less controlled environments. Our objective was to investigate if a specific motor task could reliably be detected from multi-unit intra-cortical signals from freely moving animals. Four rats were trained to hit a retractable paddle (defined as a ‘Hit’). Intra-cortical signals were obtained from electrodes placed in the primary motor cortex. First, the signal-to-noise-ratio was increased by wavelet denoising. Action potentials were then detected using an adaptive threshold, counted in three consecutive time intervals and were used as features to classify either a ‘Hit’ or a ‘no-Hit’ (defined as an interval between two ‘Hit’s). We found that a ‘Hit’ could be detected with an accuracy of 75 ± 6% when wavelet denoising was applied whereas the accuracy dropped to 62 ± 5% without prior denoising. We compared our approach with the common daily practice in BCI that consists of using a fixed, manually selected threshold for spike detection without denoising. The results showed the feasibility of detecting a motor task in a less restricted environment than commonly applied within invasive BCI research.